A COMPARATIVE STUDY ON EFFICACY OF COLLAGEN PEPTIDE ACECLOFENAC AND PARACETAMOL VERSUS ACECLOFENAC AND PARACETAMOL ALONE FOR THE TREATMENT OF KNEE OSTEOARTHRITIS. - Raju, Mareena; Johnson, Blessy K; Sharma, Ambarish; R, Bharathi D (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: The existing treatment for Osteoarthrits (OA) is symptomatic by NSAIDS are effective for reducing pain associated with OA, they do not reverse the disease. This makes way for the emergence of nutraceuticals like collagen peptide which are chondroprotective in nature. Objectives: To assess the prevalence of knee OA, efficacy of combination of collagen peptide, aceclofenac and paracetamol against aceclofenac and paracetamol alone in the treatment of osteoarthritis, the medication adherence and drug related problems in OA. Methods: A prospective observational study was carried out in the outpatients of Department of Orthopaedics, BMCH & RC and Ambarish’s Clinic, Chitradurga. A total of 154 patients suffering from OA were identified. 60 subjects of Grade I knee OA were selected for the study from 112 cases of knee OA. The subjects were divided in two groups; Group A comprised of 30 subjects who were treated with collagen peptide, aceclofenac and paracetamol (Acetaminophen) for a period of two months, with a follow up of one month and the therapy was assessed by Visual Analogue Scale(VAS). Whereas Group B of 30 subjects who were treated with aceclofenac and paracetamol for two months with a follow up of one month and assessed by VAS. Results: The prevalence of knee osteoarthritis was found to be 72.72%.Among them Grade I was 77.67%. From this 60 patients were selected for further study of which 90% were females and 10% males. At the end Group A showed better results than Group B. Acetaminophen and Aceclofenac related gastrointestinal disturbances were found in both the groups. Majority of the patients also had good medication adherences. Conclusion: The study identifies and supports the use of collagen peptide to provide symptomatic relief and can be used as adjunct therapy for OA management. Keywords: Knee osteoarthritis, nutraceuticals, collagen peptide, Visual Analogue Scale.